2015
DOI: 10.1016/j.jds.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral uracil and tegafur as postoperative adjuvant metronomic chemotherapy in patients with advanced oral squamous cell carcinoma

Abstract: Background/purpose: In this study, we evaluated the effectiveness of oral uracil etegafur (UFUR) as a postoperative adjuvant treatment for patients with advanced oral squamous cell carcinoma (OSCC). Materials and methods: The study cohort consisted 80 patients with advance cancer treated between January 2003 and December 2007. Half of the patients received oral UFUR as postoperative metronomic adjuvant chemotherapy, while the other half received no treatment. No patients received postoperative radiotherapy or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The results revealed that patients treated with metronomic UFUR had a significant reduction in the detectable viable CEP cells, which might implicate an antiangiogenesis mechanism behind the survival benefits. The toxicities were mild and manageable, with skin rash (5%) being the most common side-effect, followed by hematological side-effects (2.5%) and nausea/vomiting (2.5%) [103]. Hsieh et al [104] conducted a retrospective study of 356 stage III and IV OCSCC patients.…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that patients treated with metronomic UFUR had a significant reduction in the detectable viable CEP cells, which might implicate an antiangiogenesis mechanism behind the survival benefits. The toxicities were mild and manageable, with skin rash (5%) being the most common side-effect, followed by hematological side-effects (2.5%) and nausea/vomiting (2.5%) [103]. Hsieh et al [104] conducted a retrospective study of 356 stage III and IV OCSCC patients.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Although the enteral route for metronomic agents brings convenience and at-home treatment, it should be noted that some OCSCC patients have difficulty in swallowing. This issue matters and affects patient compliance if metronomic chemotherapy is used as adjuvant/maintenance therapy in OCSCC, which might last for 1-2 years [103,104].…”
Section: Advantages and Limitations Of Metronomic Therapy In Ocsccmentioning
confidence: 99%
“…One study set two groups including 75 mg/m² docetaxel every 21 days and 75 mg/m² docetaxel pulse 40mg AT-101 twice daily for 3 days, which was different in using of AT-101 compared with metronomic group [18]. And one study did not give other therapies after surgery which de ned as blank control [20].…”
Section: Treatment Regimensmentioning
confidence: 99%
“…Then 67 records including 9 comments or abstracts related to the aim of study were excluded. Finally, 13 records meeting criteria, including 3 randomized control trails [17][18][19], 1 cohort study [20], 4 prospective studied (3 single arm trials [21][22][23], 1 match pair analysis [24]) and 5 retrospective studies [25][26][27][28][29] were included.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation